Ontogenetic development related to parental care of a neotropical fish, pterygoplichthys ambrosettii (Siluriformes: Loricariidae) - Araujo, Renato B. [UNESP]; Langeani, Francisco [UNESP] (My University, 2020)
This study describes the main ontogenetic changes in the armored catfish Pterygoplichthys ambrosettii from newly hatched larva to adult. The relation between the degree of development of newly hatched larvae and post-larvae and parental care is discussed. Ontogenetic series containing newly hatched larvae, post-larvae, and juveniles of P. ambrosettii were obtained from the Fish Culture Station of Universidade Estadual Paulista. Adult specimens were collected from the Preto River in the upper Paraná River basin. Morphological, osteological, morphometric, and meristic data and color pattern were analyzed. The species exhibited indirect development, with a distinct post-larval stage after the larval stage. Newly hatched larvae had a well-developed yolk sac and the absence of pigmentation. The following characters underwent less change during development and can therefore be useful in taxonomical analyses: odontodes located posteriorly to the preopercle, number of plates on the lateral line, lower lip with three series of papillae, spots on the upper ray of the caudal fin, caudal fin similar to that of the adult, body ventrally covered with dermal plates and odontodes, small irregular spots on head, and typical ventral color pattern of the adult. The morphometric data revealed that most variation in body proportions occurred in less advanced developmental stages. Parental care influenced the ontogenetic development of newly hatched larvae.
Keywords: Armored catfish; Behavior; Larval development; Morphology; Neotropics